Detection of anthelmintic resistance in gastrointestinal strongyles of cattle in Thrissur district, Kerala - V. J. Merin Das; M. N. Priya; Asha Rajagopal; Bindu Lakshmanan; K. Syamala; S. Sujith (Journal of Veterinary and Animal Sciences, 2023)
Gastro intestinal parasite (GIP) infection is an economically important disease that affects cattle population worldwide and contributes to decreased productivity and profitability in the livestock sector. An important obstacle to the management of helminth infections in cattle is the failure of therapy owing to anthelmintic resistance. The present study is aimed to identify the predominant gastrointestinal strongyles in cattle of Thrissur district, Kerala and to determine the incidence of benzimidazole resistance against these gastrointestinal strongyles in organised cattle farms and small holder farmers’ herd. Coproculture studies revealed that predominant strongyle was Mecistocirrus spp. (29.75 per cent) followed by Haemonchus spp. (21.5 per cent) and Oesophagostomum spp. (13 per cent). The in vivo method of benzimidazole resistance detection by faecal egg count reduction test (FECRT) with albendazole was done in three organised cattle farms and three small holder farmers’ herd. The per cent FEC reduction in three organised farms were 38, 55 and 85 per cent and that of small holder farmers’ herd ranged between 75 - 100. This study forms the first report of anthelmintic resistance in cattle in south India and the results indicated that benzimidazole resistance was highly progressed in organised cattle farms and in a progression state in small holder farmers’ herd that necessitates the judicial utilisation of anthelmintics for the parasite control.